Alkaline phosphatase is associated with vascular depression in patients with severe white matter hyperintensities - Tao, Xi; Yin, Yuqi; Zhang, Yi; Yang, Chen; Wu, Siyuan; Tang, Wenjing; Li, Chen; Song, Tao; He, Juan (Frontiers in Neuroscience, 2024)
Background and purposeCerebrovascular disease (CVD) poses a substantial risk for depression. Elevated levels of alkaline phosphatase (ALP) serve not only as an independent predictive factor for acute cerebrovascular events and unfavorable prognoses but also as a significant predictor of depression in premenopausal women. Nevertheless, the association between elevated ALP levels and vascular depression (VDe) in patients presenting with white matter hyperintensities (WMHs) remains unclear.MethodIn a cross-sectional survey, 265 individuals diagnosed with CVD were incorporated. Baseline demographic information, fasting blood parameters, and MRI data were systematically gathered for analysis. All patients were divided into a severe WMHs (sWMHs) group and a mild WMHs (mWMHs) group based on their Fazekas score. Univariate analysis of potential variables among different subgroups of patients with scores of Hamilton Rating Scale for Depression (HAMD) was performed. Subsequently, the diagnostic effectiveness of multivariables for positive VDe within two WMHs groups was assessed using binary logistic regression. The diagnostic capability of the multivariate approach for VDe was further scrutinized through ordinal logistic regression.Results(1) Hypersensitivity C-reactive protein (hs-CRP, p = 0.031), high-density lipoprotein cholesterol (HDL-C, p = 0.038), apolipoprotein A1 (APOA1, p = 0.009), and ALP (p = 0.011) exhibited distinct expression in patients with mWMHs across varying HAMD scores. In contrast, erythrocyte counts (p = 0.024), hemoglobin (Hb, p = 0.011), hs-CRP (p = 0.002), and ALP (p = 0.021) displayed differential expression in patients with sWMHs across different HAMD scores. (2) ALP and hs-CRP combined with APOA1 or Hb can improve the diagnostic efficiency of positive VDe in sWMHs [AUC = 0.849, 95% CI (0.753, 0.946), p < 0.001] or mWMHs [AUC = 0.718, 95% CI (0.603, 0.834), p = 0.002] patients, respectively. (3) Alkaline phosphatase (ALP) [OR = 1.016, 95% CI (1.003, 1.028), p = 0.016] is correlated with VDe in patients with sWMHs, a relationship that persisted even following adjustments for age and sex.ConclusionThe amalgamation of multiple markers enhances the diagnostic efficacy of VDe through WMHs classification. Serum ALP is associated with VDe in sWMHs patients.